On ne badine pas avec la danse : les structures d’encadrement d’une fête de saint patron au début du XVe siècle en Picardie - Adrien Dubois (Transposition)
Seigneurial justices’ records contain many pieces of information still unpublished about the medieval popular way of life and its slow mutations. The judgment published hereby concerns the conflict that arose in regards of payment of minstrels having performed at a patron saint’s celebration in Picardie at the beginning of the 15th century. Along with posterior documents, it enables us to highlight the importance of controlling popular body uses at the time. In this context, minstrel’s music can be qualifed as one of the means of controlling séduction amongst the « to be married » youths.